2011
DOI: 10.5688/ajpe756115
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Care as an Introductory Pharmacy Practice Experience

Abstract: Objective. To describe the design, delivery, and impact of a geriatric introductory pharmacy practice experience (IPPE) to develop students' skills related to consultant pharmacists' roles and patient care responsibilities. Design. A required 2-unit geriatric IPPE, involving 40 hours in a geriatric-care facility, 5 reflection hours, and 12 classroom-discussion hours, was developed for first-and second-year pharmacy students. Students interviewed patients and caregivers, reviewed patient charts, triaged patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“… Students found software as useful and satisfactory tool. The pre/post assessment of knowledge revealed improvement in knowledge (p < 0.0001) Woelfel et al (2011) [ 23 ] The School of Pharmacy at the Thomas J. Long School of Pharmacy and Health Sciences; USA/Introductory Pharmacy Practice Experiences (IPPEs); first and second year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Students found software as useful and satisfactory tool. The pre/post assessment of knowledge revealed improvement in knowledge (p < 0.0001) Woelfel et al (2011) [ 23 ] The School of Pharmacy at the Thomas J. Long School of Pharmacy and Health Sciences; USA/Introductory Pharmacy Practice Experiences (IPPEs); first and second year.…”
Section: Resultsmentioning
confidence: 99%
“… PC aspect Authors Pharmaceutical care for a patient suffering from a specific disease (e.g. diabetes) Benedict & Schonder (2011) [ 22 ] Campbell et al (2012) [ 24 ] Sterrett et al (2012) [ 25 ] Katoue & Al Haqan (2013) [ 26 ] Martinez et al (2017) [ 34 ] Marvanova & Henkel (2018) [ 36 ] Dispensing the prescription in the context of correctness, verification of medical recommendations and detection of drug problems Limberger (2013) [ 27 ] Lucas et al (2013) [ 28 ] Waitzman & Dinkins (2013) [ 31 ] Gossenheimer et al (2017) [ 33 ] Nasser et al (2021) [ 39 ] Patient education (pharmacist as an educator) Lucas et al (2013) [ 28 ] Foppa et al (2021) [ 38 ] Nasser et al (2021) [ 39 ] Faustino et al (2022) [ 40 ] Patients' medicines related needs Mesquita et al (2015) [ 32 ] Faustino et al (2022) [ 40 ] Develop a pharmaceutical care plan Woelfel et al (2011) [ 23 ] Norose (2013) [ 29 ] Geriatric care Woelfel et al (2011) [ 23 ] Cultural competency Prescott & Nobel (2019) [ 37 ] …”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the other studies found in the literature that investigated the attitudes of pharmacy students toward the elderly. [23][24][25][26] These findings are encouraging given that students' attitudes toward elderly people and aging may determine the appropriateness of the care they provide when they become pharmacists. The study's findings, however, conflict with those of studies conducted among medical and dentistry students which reported that these students held negative attitudes towards the elderly.…”
Section: Discussionmentioning
confidence: 95%
“…23 A few previous studies found that geriatrics introductory and advanced pharmacy practice experiences and other education interventions improved pharmacy students' attitudes toward elderly patients. [24][25][26] Consequently, the impact of educational interventions on the attitudes of pharmacy students about older persons is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with other studies investigating pharmacy students' attitudes toward older adults. [27][28][29][30] Based on previous findings, the appropriateness of care provided by the pharmacists might be determined via their attitudes toward this population. 23 Most of the participants recruited in this study demonstrated a close connection to their grandparents and could account for the observed positive attitudes toward older patients.…”
mentioning
confidence: 99%